(untitled) (Global Journal of Science Frontier Research, 2014)
This new bee hive technology was designed, produced and pretested as a creative innovation on its structure and convenience for local bee races as we observed on some hives of this technology, they always work circular comb. The data on this particular work was measurements of the hive parts, construction challenges, and, and opportunities of the hive in the workshop, in my opinion there will be many works in near future on refining of hive parts, size, component number and comparative evaluation based on suggested areas and with other local and modern hives.